Workshop Pengembangan Media Pembelajaran untuk Menumbuhkan Nilai Agama dan Moral Serta Budi Pekerti Anak Usia Dini di Surakarta - Nurul Ilmi Azizah, Annafi; Fertiliana Dea, Leli; Intan Apriliani, Elina; Wardani, Anita; Hidayah, Nur (Seulanga: Jurnal Pengabdian Kepada Masyarakat, 2024)
This PKM activity was attended by 40 teacher representatives from several Early Childhood Education Institutions (PAUD) in Surakarta. This dedication aims to enable teachers to develop creativity in creating learning media such as Educational Tools by utilizing objects that are around such as natural materials or loosepart. The methods used are preparation, implementation, and evaluation. The preparatory methods include the formation of committees, the division of tasks and coordination with the source. The implementation method includes the presentation of material by the source and the practice of creating learning media. The evaluation phase is a discussion and a question answer between the workshop participants and the source. The result of this PKM activity is that teachers acquire practical skills in creating creative and interesting teaching materials. In addition, Teachers can develop and use a variety of appropriate learning media to teach moral and religious values of labor as a tool, as well as visual media so that learning is interesting and enjoyable for children.